2018
DOI: 10.3390/f9060361
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting Landowners of Shandong, China Based on Their Attitudes towards Forest Certification

Abstract: Forest certification is considered a viable market-based policy instrument to promote forest sustainability. It has an important role of play in meeting the objective of modern forestry development in China, which is to sustain ecological and environmental benefits of forests. To understand differences in attitudes, opinions, and interests in forest certification, this study segmented respondents of a landowner's survey in Shandong, China based on their level of interest in participating in forest certificatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…The weight loss rate is defined as Formula (6): WLR (%) = 100 × (Wb -Wa) / Wa (6) where Wa and Wb are the weight of the wood sample before and after fungus attack, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight loss rate is defined as Formula (6): WLR (%) = 100 × (Wb -Wa) / Wa (6) where Wa and Wb are the weight of the wood sample before and after fungus attack, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This is of great significance for promoting the sustainable development in society [1][2][3][4][5]. However, the drawbacks of wood, such as dimensional instability when exposed to wet conditions and biological degradation when exposed to decay fungi, limit its long-term utilization [6][7][8][9][10]. Although its biodegradable nature is beneficial, from the perspective of sustainable development wood still needs to be modified to obtain better durability when exposed to the above harsh environments [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Increased costs of certification are, thus, one of the main barriers for the adoption of forest certification for forest owners as well as for the chain of custody (CoC) level [11,43,[52][53][54][55]. The unit cost is relatively higher for small compared to large forest owners [56]; however, certified forest owners believe that certification benefits exceed costs [42,56].…”
Section: Forest Certification and Sustainabilitymentioning
confidence: 99%
“…Regarding the research of forest certification among landowners, the existing literature mostly focuses on the research areas of identifying landowners' concerns and challenges to participate in forest certification as well as investigating their perceptions and attitudes towards certification programs. For example, one key concern for landowners to have their property certified was the costs associated with certification [7][8][9][10][11][12][13][14][15][16][17][18]. To be specific, Tian et al [17] reported that increased management costs was significantly and negatively associated with landowners' willingness to participate in forest certification in Shandong Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…To be specific, Tian et al [17] reported that increased management costs was significantly and negatively associated with landowners' willingness to participate in forest certification in Shandong Province, China. Studies also showed that the stringent requirements of certification program such as requirement of a written management plan [8,10,17,18] was another landowner's concern for seeking forest certification. For example, Kilgore et al, [19] and Leahy et al [12] reported that the requirement of a forest management plan was a barrier for family landowners to adopt forest certification with a survey conducted in Minnesota.…”
Section: Introductionmentioning
confidence: 99%